THU0506 Tocilizumab Therapy in Children with Polyarthicular Course Juvenile Idiopathic Arthritis. (9th June 2015) - Alexeeva, E.; Denisova, R.; Valieva, S.; Bzarova, T.; Kseniya, I.; Sleptsova, T.; Chistyakova, E.; Chomakhidze, A.; Soloshenko, M.; Fetisova, A.; Lomakina, O.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a chronic arthritis of unknown cause with an onset before 16 years of patient age.Patients with polyarticular-course JIA (pcJIA) have risk for profound disability. Although these patients may respond to methotrexate (MTX) or biological agents approved for pcJIA, up to 30% continue to have active disease.Interleukin-6 (IL-6) is increased in the serum and synovial fluid of patients with pcJIA; IL-6 concentrations are positively correlated with the severity of joint involvement and with C-reactive protein (CRP) levels. Tocilizumab is effective drug for the treatment of rheumatoid arthritis and systemic JIA refractory to immunosuppressive drugs. Objectives: To evaluate safety and efficacy of tocilizumab treatment in children with pcJIA. Methods: Analysis of efficacy and safety tocilizumab therapy was performed in 22 patients (3 - RF+, 3-enthesitis related arthritis), whom follow up period was 6 months (n=21, tocilizumab treatment was discontinued in in 1 patient at week 3). Median age was 9, 9 years (range; 2, 9 to 17, 2 years) and median disease duration was 3, 9 years (range; 0.4 to 11, 3 years). Tocilizumab was administrated intravenously at a dose of 8 or 10 mg/kg every 4 weeks. 11 patients were treated by biologics previously. The majority of patients received concomitant DMARDs, 18 patients received methotrexate, 1-leflunomid, 1-sulfasalazin, 4- prednisolone at dose 0.5 (0.5; 1) mg/kg/day. 3 patients had uveitis: 2-not active and 1-active. Efficacy end points included the American College of Rheumatology (ACR) Pediatric criteria for improvement 30 (ACR30), ACR50, ACR70, ACR90 and criteria of inactive disease and index JADAS10. During the follow-up period, significant side-effects were sought. Results: The ACR Pedi 30, 50, 70, 90 and 100 improvement were achieved by 100% (n=21), 85% (n=18), 52% (n=11), 24% (n=5), and 14% (n=3) of patients at Week 24 (n=21), respectively. Inactive disease was achieved by 7/21 (33%) of patients at week 24. The JADAS10 decreased from 26, 5 (19, 8; 28, 8) to 6, 2 (1, 4; 18, 9) at week 24 (p<0.001). The number of platelets decreased from 432x10 9 /l (348; 505) to 253 (214; 281) at week 24 (p<0.001), number of leucocytes – from 9, 0 x10 9 /l (7, 8; 9, 0) to 6, 3 (4, 7; 7, 1) at week 24 (p<0.01); level of hemoglobin increased from 105 (97; 120) g/l to 127 (120; 132) at week 24 (p<0.01).The frequently observed non-severe adverse events were nasopharyngitis, upper respiratory tract infections and gastroenteritis. No cases of opportunistic infections, malignancies or death were reported. 2 patients had incidences of neutropenia, 1 – trombocytopenia. Tocilizumab treatment was discontinued in 4 patients during the follow-up 24 weeks period. The causes for cancellation were lack of efficacy (n=3) at week 24, infusion reaction (n=1) at week 12. 3 patients were switched to antiTNF blockers and 1 – to abatacept. Conclusions: Tocilizumab treatment provided clinically meaningful improvement for patients with pcJIA. Tocilizumab induced remission of arthritis and normalized laboratory parameters of the disease activity The safety profile of tocilizumab was consistent that seen in other studies. Disclosure of Interest: None declared